(untitled) - McRae, John (Cambridge, 1995)
The book is organised thematically, covering such topics as family, Environment, Rebellion, and Women. There is a minimum of three texts in each unit and the related activities are varied and thought-provoking, to simulate and sustain discussion
Keywords: English language,English language; Study and teaching,Textbooks for foreign speakers